Application of agar-based adsorbents in the removal of dyes and heavy metals from wastewater: Current advances, challenges, and future perspectives - El Messaoudi, Noureddine; miyah, Youssef; Georgin, Jordana; S P Franco, Dison Stracke Pfingsten; Temur Ergan, Başak; Mbanga, Bienvenu Gaël Fouda; Knani, Salah (Elsevier B.V., 2025)
Excessive release of toxic dyes and heavy metals into water bodies has become a significant environmental and public health issue. Therefore, research into environmentally friendly, low-cost, and efficient adsorbents has been a critical area of study in wastewater treatment. This review discusses agar-based adsorbents for the removal of dyes and heavy metals from wastewater, highlighting agar as a biodegradable and renewable polysaccharide derived from red algae, rich in functional groups that enhance its adsorption potential. It focuses on recent advancements in agar modification, i.e., cross-linking, grafting, and composite preparation using nanomaterials, to enhance its mechanical strength, selectivity, and adsorption capacity. The various methods of synthesis and their impact on the adsorption capacities of contaminants are critically reviewed. Although promising, others, such as regeneration frontiers, mechanical instability in water, and scalability boundaries, still prevail. Overall, this paper provides useful information on the latest developments and emphasizes the importance of interdisciplinary microbiology research to use agar-based adsorbents in real wastewater treatment. © 2025 Elsevier B.V., All rights reserved.
Keywords: Adsorption; Agar; Dyes; Heavy metals; Wastewater treatment